Effect of processing parameters in fabrication of Co-Ni- Fe coated mild steel for welding plate application \ Mohd Adham Akmal Tukiran - Tukiran, Mohd Adham Akmal (2016)
Mild steels are used widely in the manufacturing industries such as welding plate. The major problem of mild steel is the corrosion which occurred easily when they are exposed to the environment. Replacement or repair of corrosion damaged equipment is therefore demanded in the industry. Previous published literature showed that Cobalt-Nickel-Iron (Co-Ni-Fe) enhanced the corrosion behavior of metals. This study investigated the effect of process parameters in fabrication of Co- Ni-Fe coated mild steel. The mild steels are being coated to prevent the corrosion occurrence that will affect the surface strength of the welded mild steel. A low cost electrodeposition method is applied to the synthesis of the Co-Ni-Fe as a protective coating layer on the mild steel. The electrodeposition was conducted at controlled o temperature of 50 C±5°C in an acidic environment of pH 3. Process variables are the key factor in controlling the fabrication process. The influence of deposition times (15, 20 and 30 min) and current density (11, 22, 33, and 87mA/cm ) towards the characteristics and physical properties such as phase and crystallographic structure, surface morphologies, particle size and elemental composition were studied. This is important to study the processing parameter in order to optimize the performance of 2 final product. From Co-Ni-Fe nanoparticles deposited at 30 minute with 87 mA/cm current density produced the highest Vickers microhardness of 202.96 HV and also experienced the slowest corrosion rate. FESEM and XRD had been shown reduction in crystallite size and EDX had shown reduction of oxygen composition as deposition time and current density was increased. The XRD obtained the phase structure of FCC and BCC. The deposition time and current density also influenced the surface roughness. It is found that the increment of time deposition and current density had improved the microhardness and corrosion resistance behavior of Co-Ni- Fe coatings. This may due to the homogenous and complete protection coating on the mild steel.